Quantitative morphological characteristics of platelet hemostasis in patients with type 1 and 2 diabetes mellitus depending on the glomerular filtration rate. - Pertseva, T. O.; Tverdokhlib, I. V.; Chub, D. I. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. The use of only a complex of clinical and laboratory parameters characterizing the state of the kidneys and a lipid profile profile with anamnestic data to determine the initial manifestations of functional renal insufficiency is not sufficient. This necessitates the search for new, more informative markers for the risk of development and progression of diabetic nephropathy in type 1 diabetes mellitus patients, which may be endothelial dysfunction markers and morphological parameters of thrombocyte hemostasis. Objective. The purpose of the study is to analyze the quantitative parameters of platelet hemostasis in patients with diabetes mellitus type 1 and type 2, depending on the velocity of glomerular filtration rate. Methods. Transmission electron microscopy and phase contrast microscopy quantitatively assessed the state of platelet hemostasis in the blood of 66 patients with type 1 diabetes mellitus and 58 patients with type 2 diabetes mellitus, depending on the velocity of glomerular filtration rate. Results. Quantitative characterization of the morphological features of platelet hemostasis revealed early signs of damage to the platelet structure, which occur at normal levels of glomerular filtration rate in patients with diabetes mellitus type 1 and type 2. Increased degranulation of alpha-granules and the growth of circulating platelet aggregates in the setting of significant activation of thrombocytes in the hyaline type are the most sensitive signs of hemostasis disorder in patients without clinical signs of diabetic kidney disease. The degree of pathomorphological changes in platelet count in patients with type 2 diabetes mellitus is higher than that of type 1 diabetes mellitus. With the progression of diabetic nephropathy, there is a significant deepening of platelet hemostasis disorders with the involvement of ultrastructural lesions of erythrocytes and leukocytes, massive platelet degranulation, the formation of numerous complex platelets, consolidation of correlations between the greater part of morphological parameters characterizing the hemostatic profile in patients with diabetes mellitus 1 and 2 type. Conclusion. Morphological changes in platelet hemostasis in patients with diabetes mellitus occur to the clinical manifestations of diabetic kidney disease and clearly correlate with the profundity of diabetic nephropathy at the stages of its development.